1972
DOI: 10.1039/f29726800144
|View full text |Cite
|
Sign up to set email alerts
|

Energy partition in the γ-radiolysis of gaseous H2S + N2O mixtures

Abstract: Measurement of ion yields Gm(= lOO/W,), where W, is the average energy required to produce an ion pair in the mixture) in gaseous H2S-N20 mixtures indicates that the energy partition parameter " a " = 0.53 holds for mixtures of stopping power fraction Z = P1[P1+(S2/S1)P21 from 0.15 41.0, and perhaps over the whole range of 2. PI and P2 are the partial pressures and S1 and S2 are the stopping powers relative to air of H2S and N20 respectively. The radiation yields of H2 and N2 in the mixtures G(H,), and G(N2)m … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1973
1973
1973
1973

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Rcently several studies of the radiolysis of hydrogen sulfide have been reported (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) and we have proposed a mechanism based on our measurements at high dose rates (13). While this mechanism is in general agreement with the observed yields there are problems which need further investigation.…”
Section: Introductionsupporting
confidence: 75%
“…Rcently several studies of the radiolysis of hydrogen sulfide have been reported (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) and we have proposed a mechanism based on our measurements at high dose rates (13). While this mechanism is in general agreement with the observed yields there are problems which need further investigation.…”
Section: Introductionsupporting
confidence: 75%